La pratique de la réflexivité, un moyen de satisfaire aux nouvelles exigences liées à la sobriété numérique en formation continue des enseignants - Amadou Yoro Niang (Centre National d'Enseignement à Distance, 2023)
In this 21st century, teacher trainers are faced with two systems of ambivalent constraints. They must, on the one hand, obey the injunctions of the educational authorities, by imperatively carrying out digitization in continuing education and, on the other hand, integrate the challenges of digital sobriety into their practices. In this context, we could simply reduce the digital footprint in training in quantitative terms. But for our part, we wanted to explore another path. Indeed, can we not draw inspiration from the paradigm of the "reflective practitioner" and examine whether there is not a means of encouraging a considerable reduction in the number of FADs and reasoning in this way in environmental issues related to digital sobriety. It is a question of questioning the use of reflective practice, and wondering if it cannot be the subject of a device among trainers allowing them to find a compromise in the face of these contradictory injunctions. The methodology applied is qualitative and involves interviews with 3 masters and 1 trainer, the analysis of 3 trainer/trainee interview films and reflective texts. The study shows that if teachers used reflective practice, it would promote digital sobriety.